A(r)cadie heureuse? Space, Place, and Engaged Pastoral in Zachary Richard’s Feu - Rachel A Paparone (Studies in 20th & 21st Century Literature, 2018)
Cajun musician, poet, and activist Zachary Richard is a vocal advocate for the revival of the Cajun French language and for the preservation of the environment. In his 2001 collection of poetry, Feu (Fire), Richard unites three themes that initially seem distinct: the promotion of Cajun French as his community’s native language, the exploration and memorialization of his Acadian roots, and environmental exploitation. On closer inspection, however, it becomes clear that throughout the collection Richard frames energy production as an act of imperial aggression, thus aligning the historical persecution of the Acadians and the linguistic and cultural marginalization of the Cajuns, with resource appropriation in Francophone North America. This article examines ways in which Richard deconstructs myths of Arcadia that shaped the Acadian and Cajun experience, and problematizes the use of pastoral rhetoric to promote imperial expansion in North America. By refocusing the reader’s attention onto populations, landscapes, and histories marginalized by power struggles, often within a single poem or a single series of poems, Richard creatively intervenes in the typically static hegemonic narrative of resource domination in North America, thereby forcing a reevaluation of what it means to occupy physical and rhetorical space, an issue that has been seen as central to the modernization of the pastoral genre.
Keywords: pastoral; engaged literature; Zachary Richard; Cajun poetry